PENGARUH PENGETAHUAN KEWIRAUSAHAAN, SELF EFFICACY, DAN LINGKUNGAN KELUARGA TERHADAP MINAT BERWIRAUSAHA DI SMK NEGERI 2 KOTA MOJOKERTO: THE EFFECT OF ENTREPRENEURIAL KNOWLEDGE, SELF EFFICACY, AND FAMILY ENVIRONMENT ON ENTREPRENEURIAL INTEREST IN VOCATIONAL HIGH SCHOOL 2, MOJOKERTO CITY - Lisa Adelia, Ananda; Sudarwanto, Tri (Jurnal Pendidikan Tata Niaga (JPTN), 2025)
Vocational high school students’ interest in pursuing entrepreneurship is still relatively low, even though they have received entrepreneurship material during the learning process at school. This condition indicates the need for a more in-depth study to understand the factors that can influence this interest. Therefore, this study aims to examine the influence of entrepreneurial knowledge, self-efficacy, and family environment on entrepreneurial interest in grade XII students at SMK Negeri 2 Mojokerto City. The research method used is a quantitative approach with data collection techniques through surveys. Data analysis was carried out using multiple linear regression with the help of SPSS software version 25. Based on the analysis results, it was found that entrepreneurial knowledge has a positive and significant effect on students’ interest in entrepreneurship. Meanwhile, self-efficacy does not have a significant effect. The family environment variable shows a significant but negative influence on entrepreneurial interest. These three variables, when analyzed simultaneously, are proven to make a significant contribution to students’ interest in entering the business world. These findings underscore the importance of synergy between the role of schools and family support in creating a conducive atmosphere to foster an entrepreneurial spirit among students. The results of this study are expected to be a consideration for schools and policy makers in designing more targeted learning strategies, in order to form a strong entrepreneurial character in vocational school students.